Fungi that further fertility - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Increasing crop production and land productivity in the tropics is essential if the food demand of the growing population in these areas is to be met. Of all the soil-related constraints on crop production, low soil fertility is the most severe on...